Alcohol‐related hepatocellular carcinoma is a heterogenous condition: Lessons from a latent class analysis. (11th May 2022) - Costentin, Charlotte E.; Minoves, Mélanie; Kotzki, Sylvain; Farges, Olivier; Goutté, Nathalie; Decaens, Thomas; Bailly, Sébastien
Abstract: Background: Alcohol‐associated hepatocellular carcinoma (AL‐HCC) poor prognosis has been attributed to diagnosis at a later stage. However, host factors and specific health trajectories have been associated with severe outcomes in alcohol‐related liver disease. We hypothesize AL‐HCC is not a homogeneous condition but encompasses subgroups yielding different outcomes. Aims: Our aim was to provide a first attempt at a clinical phenotyping of AL‐HCC. Methods: We analysed data for the calendar years 2007–2013 from the French nationwide administrative hospital database. We selected patients with AL‐HCC only. Clustering of AL‐HCC phenotypes was performed by latent class analysis (LCA). Results: The study included 11 363 patients with AL‐HCC, mainly male (89.6%), median age 67 years [IQR: 61; 74] of which 71.2% had at least one metabolic comorbidity. Five phenotypes were identified. Phenotype 1 (41.4%) displayed high rates of unrecognized cirrhosis prior to HCC diagnosis (81%), low rates of metabolic comorbidities (diabetes 13%), and mostly compensated liver disease at HCC diagnosis while the four other phenotypes displayed high rates of metabolic comorbidities (diabetes up to 100%), various patterns of liver disease trajectories and overall 42% unrecognized cirrhosis. In adjusted survival analysis, compared to phenotype 1, risk of death after HCC diagnosis was significantly different for all phenotypes. Conclusion: LCA uncovers AL‐HCC is a heterogeneous condition with distinct phenotypes yielding specific survival outcomes. Frequent unrecognized cirrhosis prior to HCC underlines the urgent need for implementing strategies to identify the underlying liver disease prior to HCC onset in patients with documented alcohol use disorders and metabolic comorbidities.